2017
DOI: 10.1111/jch.13061
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of renin‐angiotensin system polymorphisms with ambulatory and central blood pressure in patients with hypertension

Abstract: | INTRODUCTIONIt is well known that the renin-angiotensin system (RAS) plays a cen- found that the T allele of C-5312T single nucleotide polymorphism and the haplotype containing T was associated with elevated BP levels in healthy humans, and this association of renin 5312 C/T genotype with BP was independent of age and sex.3 Another longitudinal studyshowed that the C allele carrier in the A1166C polymorphism had a 35% more pronounced increase in aortic arterial stiffness over a 16-year period than the AA all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…The systemic RAS is an endocrine system with important roles in regulating blood pressure and electrolyte homeostasis ( Ahn et al, 2017 ; Han et al, 2017 ). Various organs and tissues, including bone, have also been shown to have local tissue-specific RAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The systemic RAS is an endocrine system with important roles in regulating blood pressure and electrolyte homeostasis ( Ahn et al, 2017 ; Han et al, 2017 ). Various organs and tissues, including bone, have also been shown to have local tissue-specific RAS.…”
Section: Discussionmentioning
confidence: 99%
“…The systemic renin–angiotensin system (RAS) has been widely investigated because of its roles in the regulation of blood pressure, electrolyte homeostasis, and the development of hypertension ( Ahn et al, 2017 ; Han et al, 2017 ). Several human studies suggested that hypertension is associated with low bone mineral density and increased risk of fracture ( Li et al, 2017 ; Lian et al, 2017 ; Ye et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, significant genotype-sex interactions were detected only among Mexican Americans (positive associations with SBP and hypertension in women, but not in men), while this was not observed for non-Hispanic white persons and non-Hispanic black persons. Multivariate regression analysis by Han et al (2017) demonstrated that the ACE DD genotype was independently associated with 24□hour SBP, 24□hour DBP, central SBP, and central augmentation index in Chinese patients recruited at Shandong Provincial Hospital in the Jinan area. Thus, it can be concluded that the influence of variation in the ACE gene on interindividual variation in blood pressure is dependent on contexts that are indexed by gender, age, and measures of body size (Turner et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Blood pressure and electrolyte balance are tightly controlled by the renin-angiotensin system (RAS). Hypertension is significantly influenced by RAS activation ( 26 , 27 ). RAS is a hormonal cascade in which renin from the kidney cleaves angiotensinogen from the liver into inactive angiotensin (ANG) I.…”
Section: Introductionmentioning
confidence: 99%
“…Pro-inflammatory chemicals including IL-6 and TNF-a, which encourage bone resorption, is further stimulated by ANG II. Several studies showed angiotensin II receptor blockers (ARB) bind to AT1R and block ANG II, preventing pathological changes (27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%